2017
DOI: 10.1016/j.pdpdt.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence visualization efficacy for detecting oral lesions more prone to be dysplastic and potentially malignant disorders: a pilot study

Abstract: This study indicates fluorescence visualization is capable of improve inexperienced professionals' efficacy for early detecting oral lesions more prone to be dysplastic and oral potentially malignant disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 14 publications
3
13
0
2
Order By: Relevance
“…These systems can noninvasively detect a region of the oral cavity mucosa to determine the changes associated with oral cancer. 38 The several studies having trials on detecting OSCC and oral potentially malignant disorders (OPMD) using VELscope, Identafi, and EVINCE seem to agree with certain consistent results in individual research and show the possibilities of OSCC and OPMD early detection potentially with autofluorescence images. 16 Roblyer 36 proposed a simple objective method to classify regions of interest (ROIs) and evaluate the sensitivity and specificity relative to the histopathology of oral neoplastic lesions through multispectral digital microscopy.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…These systems can noninvasively detect a region of the oral cavity mucosa to determine the changes associated with oral cancer. 38 The several studies having trials on detecting OSCC and oral potentially malignant disorders (OPMD) using VELscope, Identafi, and EVINCE seem to agree with certain consistent results in individual research and show the possibilities of OSCC and OPMD early detection potentially with autofluorescence images. 16 Roblyer 36 proposed a simple objective method to classify regions of interest (ROIs) and evaluate the sensitivity and specificity relative to the histopathology of oral neoplastic lesions through multispectral digital microscopy.…”
Section: Introductionsupporting
confidence: 59%
“…16,18,27,[32][33][34][35] A handheld device, the VELscope, was proposed for clinicians to noninvasively direct the fluorescence images of oral cavity tissues. 16,33,35,[37][38][39][40][41][42][43][44][45][46][47] Some studies observed the spectra of autofluorescence on different anatomical sites and found some characteristics between different sites. The results indicated that quantitative autofluorescence imaging can provide a noninvasive and objective method for detecting oral neoplasia.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of OED or discrimination between benign, dysplastic or malignant oral mucosal lesions has been extensively researched, with literature reporting overall poorer specificity along with significant heterogeneity in published studies (Awan & Patil, ; Lingen, Tampi et al, ; Luo et al, ). The results from this review are in keeping with previous studies assessing discrimination between oral mucosal lesions, demonstrating significant heterogeneity and variation in reported efficacy (COE alone: sensitivity: 5.9%–96.6%; specificity: 42.9%–97.8%, OFI alone: sensitivity: 30%–100%; specificity: 12.5%–93%, combined examination: sensitivity: 46%–100%; specificity: 6%–74%; Amirchaghmaghi et al, ; Awan et al, ; Awan et al, ; Babiuch et al, ; Betz et al, ; Chiang et al, ; Farah et al, ; Hanken et al, ; Jayaprakash et al, ; Koch et al, ; Lalla et al, ; Lane et al, ; Marzouki et al, ; Mehrotra et al, ; Moro et al, ; Paderni et al, ; Petruzzi et al, ; Rana et al, ; Sawan & Mashlah, ; Scheer et al, ; Simonato et al, ). It is also interesting to note that all studies with a low risk of bias except Paderni et al reported an overall reduction in specificity using OFI compared to COE alone and at present OFI cannot replace histopathological assessment of a tissue biopsy as the gold standard for the diagnosis of OED or OSCC (Bhatia et al, ; Farah et al, ; Lalla et al, ; Paderni et al, ; Rana et al, ).…”
Section: Discussionsupporting
confidence: 83%
“…A study by McIntosh et al noted better visualisation of lesions using white light emitted from a LED headlight compared to standard dental incandescent yellow light during COE (McIntosh et al, ). It is interesting to note that in the current review, only 9 of 27 studies utilised white light to conduct COE (Betz et al, ; Cânjău et al, ; Hanken et al, ; Jayaprakash et al, ; Lalla et al, ; Lane et al, ; Paderni et al, ; Simonato et al, ; Sweeny et al, ). Given the pre‐existing subjectivity of COE, optimisation of COE through the standardised use of white LED light to conduct COE may enhance visualisation of oral mucosal lesions in COE alone, and in turn aid in improving accuracy of diagnosis of oral mucosal lesions.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation